ANALISIS KEMAMPUAN KONEKSI MATEMATIS DAN SELF ESTEEM SISWA SMA DI KABUPATEN BANDUNG BARAT - Fitriah, Aidah; Aripin, Usman (IKIP Siliwangi, 2019)
The purpose of this study was to determine the extent of the mathematical connection ability and self esteem of high school students in West Bandung. In this study the method used is a Descriptive Qualitative Method that aims to analyze the results of student answers to mathematical connections as well as high school student self-esteem search questionnaires in West Bandung. The subjects of this study were 20 students in one of the high schools in West Bandung. As for the tests given in the form of questions about mathematical connections as many as 4 questions and non-test questions self-esteem is intended for each student. The results of the analysis obtained based on written description tests are the mathematical connection ability of high school students in West Bandung on indicators using the relation between mathematical topics by 23%, in the second indicator that is to find connections between procedures to other procedures equivalent to 30%, then on the indicator connecting with other fields of study were 12% and on indicators applied mathematics to everyday problems, by 20%. Meanwhile for self esteem students in high school in West java based on self esteem search questionnaire is still relatively low.